THE EMBODIMENT OF THE IDEA OF PROFILE EDUCATION IN SECONDARY SCHOOL IN THE SECOND HALF OF 1980-IES - EARLY 90-IES - Валентина Кушнір (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article considers ways of implementation of profile education in high school during the second half of the 80's - early 90-ies of the XX century. It was found that during that period profiling of secondary education took place in several ways: creation of classes with intensive study of one or more subjects, creation of specialized classes focused on a single subject and the creation of specialized university oriented classes. It was shown that introduction of profile differentiation contributed to the creation of new types of schools such as gymnasium and lyceum.